1984
DOI: 10.1104/pp.75.3.726
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Alkaloid-Producing Cell Cultures of Periwinkle (Catharanthus roseus)

Abstract: A procedure for cryogenic storage of alkaloid producing cell lines of periwinkle, Catharanthus roseus (L.) G. Don, has been developed. The procedure differs from established cryopreservation protocols in several aspects. Specifically, 4-day-old suspension subcultures of three cell lines were precultured in nutrient media supplemented with 1 molar sorbitol for 6 to 20 hours. The cells were then incubated in nutrient media with 1 molar sorbitol plus 5% DMSO in an ice bath for 1 hour and, thereafter, were frozen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 24 publications
0
34
0
1
Order By: Relevance
“…First, sugars accumulate during cold acclimation in many species (Levitt, 1980), including bromegrass (Tanino et al, 1990). Also, cryoprotection studies have demonstrated that sorbitol is one of the most effective cryoprotectants (Chen et al, 1984). It has been suggested that there is a requirement for the up-regulation of genes involved with sugar metabolism during cold acclimation (Guy, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…First, sugars accumulate during cold acclimation in many species (Levitt, 1980), including bromegrass (Tanino et al, 1990). Also, cryoprotection studies have demonstrated that sorbitol is one of the most effective cryoprotectants (Chen et al, 1984). It has been suggested that there is a requirement for the up-regulation of genes involved with sugar metabolism during cold acclimation (Guy, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…As an extreme example, in a previous study from this laboratory, Chen and associates (4,5) reported that 7.2% of Catharanthus roseus and 2.5% of Triticum aestivum suspension cells survived immersion in liquid nitrogen without the addition of cryoprotectants. From this observation it was speculated that severe freezing stress might be used to isolate freezing-tolerant variants from a heterogeneous population of cells.…”
mentioning
confidence: 97%
“…It has been reported that the various desired properties which the cells have are retained after the cryostorage in LN,9 -15) but by the present methods all cells do not recover from the cryostoragey, [13][14][15] This suggests the possibilities that freezing-resistant cells are obtained by the present methods and that the various desired properties which the cells have are lost after the cryostorage.…”
Section: Discussionmentioning
confidence: 62%